Efek Zeolit untuk Produksi Tar dan Char pada Pirolisis Rotary Kiln - Wijayanti, Widya (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2021)
This study aims to investigate the effect of zeolite as a catalyst to enlarge biomass decomposition in the pyrolysis process. It absorbs a high water content in the biomass, besides it makes the easier breaking of biomass molecules to maximize the biomass decomposition into the expected pyrolysis products; tar and char. In addition, to decompose the biomass molecules, the zeolite also stimulates the rate of heat transfer due to its ability to hold and release the heat. If the previous research pyrolysis was conducted in a fixed bed reactor, in this study, it will be carried out rotary kiln as a pyrolysis furnace. If the fixed bed reactor the heat transfer was dominated by conduction, the heat transfer in the rotary kiln is more controlled by the convection and radiation transfer due to stirring and turning of biomass by the kiln. In the study, the biomass used was mahogany with an initial weight of 150 grams. The rotary kiln rotated at 10 rpm and the heating rate during the pyrolysis process was around 0.1483°C/s. The pyrolysis temperatures used were varied as 250°C, 350°C, 450°C. Meanwhile, the percentage of zeolites used from 0% to 60% with a mesh size of 80. The results showed that zeolites were able to increase tar production and maximize the reduction of char as an effect of the Bronsted-Lowry and Lewis reaction in the process of catalytic cracking. The maximum production of tar and char production was also supported by the process of convection and radiation from the rotary kiln wall increasing the rate of heat transfer to decompose the biomass.